The effect of big five personality, self-efficacy and safety culture on adverse driving behaviour among motorists in Malaysia - Nur Shazwani, Rosli (2018)
Adverse driving behaviour has been found to be the main contributor to most of the road traffic accidents in the country. The growing number of people killed or seriously injured on these accidents has also becoming a cause of concern for the government. Thus this study aimed to investigate the effect of the five facets of Big 5 personality, self-efficacy and safety culture on adverse driving behaviour among motorists in Malaysia. The study also aimed to determine the mediating effect of selfefficacy and moderating role of safety culture on the relationship between Big 5 personality and adverse driving behaviour. A conceptual framework underpinned by two theories; General Aggression Model (GAM) and Social Cognitive Theory (SCT) was developed and nine hypotheses were postulated and tested. This study applied an intercept survey method to gather data from designated R & R areas in the Klang Valley. A total of 3 1 1 usable responses were collected and these were analysed using Partial Least Sauares (PLS SEM). Several substantive findin-gs were revealed. First, four of the five dimensions of Big five personality; agreeableness, conscientiousness, neuroticism and openness to experience as well as self-efficacy and safety culture were significantly related to adverse driving behaviour. Only extraversion was not found to be significantly related. Second, this study revealed that self-efficacy partially mediated the relationship between Big 5 personality and adverse driving behaviour, and safety culture moderated the relationship between Big 5 personality and adverse driving behaviour. These findings demonstrated that the two theories used to underpin this study were affirmed and validated. Finally, this study concluded with the discussion on the theoretical and practical implications on the findings, the study limitations and suggestions for future research.